2018
DOI: 10.3389/fnagi.2017.00434
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Effects of Lithium and a GSK-3 Inhibitor on Neuronal Oscillatory Activity in Prefrontal Cortex and Hippocampus

Abstract: Glycogen synthase kinase-3 (GSK-3) plays a critical role in cognitive dysfunction associated with Alzheimer’s disease (AD), yet the mechanism by which GSK-3 alters cognitive processes in other disorders, such as schizophrenia, remains unknown. In the present study, we demonstrated a role for GSK-3 in the direct regulation of neuronal oscillations in hippocampus (HIP) and prelimbic cortex (PL). A comparison of the GSK-3 inhibitors SB 216763 and lithium demonstrated disparate effects of the drugs on spatial memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 148 publications
0
11
0
Order By: Relevance
“…3b ). Reportedly, AKT and GSK3β are linked to Li effects on glucose uptake [ 29 ]; therefore, we determined the effects of Li with low-intensity (12 m/min, Li/Low-Ex) for 20 min and moderate-intensity (20 m/min, Li/Mo-Ex) exercise for 40 min on AKT and GSK3β protein content. We found that Li with Mo-Ex significantly decreased muscle glycogen levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3b ). Reportedly, AKT and GSK3β are linked to Li effects on glucose uptake [ 29 ]; therefore, we determined the effects of Li with low-intensity (12 m/min, Li/Low-Ex) for 20 min and moderate-intensity (20 m/min, Li/Mo-Ex) exercise for 40 min on AKT and GSK3β protein content. We found that Li with Mo-Ex significantly decreased muscle glycogen levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The use of genetically modified mice has implicated GSK-3 in a variety of higher cognitive functions, such as spatial learning and memory (Hernandez et al, 2002;Liu et al, 2003), novel object recognition memory (Engel et al, 2006;Pardo et al, 2015) and social behaviors (Khlghatyan and Beaulieu, 2020). In terms of pharmacology, GSK-3 inhibitors lead to enhanced memory in the passive avoidance task (Yuskaitis et al, 2010), cued fear conditioning (Watase et al, 2007;Lipina et al, 2013), spatial learning (Nguyen et al, 2017) and object recognition memory (Lipina et al, 2013). The mechanism that likely underlies GSK-3's role in these cognitive processes is altered synaptic plasticity (Bradley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The consistent demonstration of increased GSK-3β activity in disorders of cognitive decline, coincident with alterations in neural oscillatory function, suggests a potential coupling of the two mechanisms. Indeed, this idea is supported by our previous evidence showing that the systemic and short-term pharmacological inhibition of GSK-3 in rats altered neural oscillatory patterns within the PFC and HIP, that were associated with improved learning and memory [44]. This study sought to expand on those findings to evaluate a direct role for GSK-3β within the PFC or HIP in the regulation of neural oscillatory activity and learning and memory processes.…”
Section: Introductionmentioning
confidence: 79%